2022
DOI: 10.3389/fcell.2022.875124
|View full text |Cite
|
Sign up to set email alerts
|

USP13: Multiple Functions and Target Inhibition

Abstract: As a deubiquitination (DUB) enzyme, ubiquitin-specific protease 13 (USP13) is involved in a myriad of cellular processes, such as mitochondrial energy metabolism, autophagy, DNA damage response, and endoplasmic reticulum-associated degradation (ERAD), by regulating the deubiquitination of diverse key substrate proteins. Thus, dysregulation of USP13 can give rise to the occurrence and development of plenty of diseases, in particular malignant tumors. Given its implications in the stabilization of disease-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 104 publications
(186 reference statements)
0
11
0
Order By: Relevance
“…24,27,41 USP13 is a deubiquitinase that modulates cancer progression, immune inflammatory response, metabolism disorder. 28 Several studies have shown that USP13 exerted important functions in modulating lung fibrosis and ECM deposition. Knockdown of USP13 accelerated lung fibroblasts phenotypic changes and contributed to pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,27,41 USP13 is a deubiquitinase that modulates cancer progression, immune inflammatory response, metabolism disorder. 28 Several studies have shown that USP13 exerted important functions in modulating lung fibrosis and ECM deposition. Knockdown of USP13 accelerated lung fibroblasts phenotypic changes and contributed to pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin-specific protease 13 (USP13) is a vital factor in innate immune responses, energy metabolism, autophagy, DNA damage response in different diseases, and can act as a tumor promoter in cancers. 28 Reports have found that USP13 was critical in the pathogenetic mechanism of pulmonary fibrosis, and knockdown of USP13 promoted lung fibroblasts phenotypic changes and contributes to pulmonary fibrosis. 29,30 Besides, USP13 overexpression reversed the repression of Spautin-1-induced autophagy and ferroptosis in cerebral ischemia-reperfusion injury.…”
mentioning
confidence: 99%
“…Ataxin 3 has been reported to directly interact with Parkin and regulates its ubiquitylation [ 72 , 73 , 75 ]. Ataxin 3 has a preference for K63-linked Ub chains and plays an important role in DNA repair and endoplasmatic reticulum-associated degradation [ 72 ].…”
Section: Deubiquitinating Enzymes (Dubs) That Regulate Parkin Functionmentioning
confidence: 99%
“…Ataxin 3 has been reported to directly interact with Parkin and regulates its ubiquitylation [ 72 , 73 , 75 ]. Ataxin 3 has a preference for K63-linked Ub chains and plays an important role in DNA repair and endoplasmatic reticulum-associated degradation [ 72 ]. The catalytic activity of Ataxin 3 is regulated via its N-terminal Josephin domain, whereas the C-terminal domain containing the Ub-interacting motif controls which interacts with different substates including Parkin [ 72 , 75 ].…”
Section: Deubiquitinating Enzymes (Dubs) That Regulate Parkin Functionmentioning
confidence: 99%
See 1 more Smart Citation